Effects of Physical Activity on Cardiotoxicity and Cardio respiratory Function in Cancer Survivors Undergoing Chemotherapy: A Systematic Review and Meta-Analysis - Kang Chen MS; Hui Guan MS; Meixia Sun MS; Yukun Zhang MS; Wenwen Zhong MS; Xiaonan Guo MS; Anqi Zuo MS; He Zhuang PhD (Integrative Cancer Therapies)
Introduction: Physical activity, as a promising complementary therapy, has shown considerable potential for reducing chemotherapy-related cardiotoxicity (CTRCT) and enhancing cardiorespiratory function (CRF). This study aimed to systematically assess the effects of physical activity on CTRCT and CRF in various cancer survivors receiving chemotherapy. Methods: A systematic review and meta-analysis was conducted. A literature search was conducted across 8 databases from inception to January 2024 and was limited to the English and Chinese languages. Statistical analysis was conducted using RevMan 5.3 and Stata 17.0 software. Results: Sixteen randomized controlled trials (RCTs) were included in the systematic review and 15 RCTs were included in the meta-analysis. Among various cancer survivors undergoing chemotherapy, physical activity markedly increased absolute oxygen uptake (VO2peak or VO2max; WMD = 292.99, 95% confidence interval [CI]:87.87 to 498.12, P  = .005), with significant effects of subgroup analysis at 4 to 10 weeks ( P  = .02) or over 16 weeks ( P  < .01), moderate-to-high or high intensity training (both P  < .0001), patients with breast cancer ( P  = .009) and reported CTRCT ( P  = .007); relative VO2peak or VO2max(WMD = 3.30, 95%CI: 2.02 to 4.58, P  < .00001), with significant effects of subgroup analysis at 10 to 16 weeks or over 16 weeks, moderate-to-high or high intensity training, patients with breast cancer, with or without reported CTRCT and exercise during chemotherapy (all P  < .01); E/A values (WMD = 0.11, 95%CI:0.03 to 0.18, P  = .007) and flow-mediated dilatation (WMD = 2.71, 95%CI:1.49 to 3.94, P  < .0001). Compared to the control group, physical activity had no significant improvement in E/e’ values ( P  = .50), NT-proBNP ( P  = .12), hs-cTn ( P  = 3.83), left ventricular ejection fraction (WMD = 2.89, 95%CI: −3.28 to 9.06, P  = .36) with non-significant effects being independent of exercise intensity or duration, with or without CTRCT and cancer types (all P  > .05), and global longitudinal strain (WMD = 0.37, 95%CI: −0.20 to 0.94, P  = .20) with non-significant effects being independent of exercise duration and cancer types(both P  > .05). Conclusions: Physical activity may be an effective complementary therapy to improve CRF and CTRCT in various cancer survivors, particularly during medium to long duration and moderate-to-high and high intensity exercise with concurrent chemotherapy.